EFEKTIVITAS REHABILITASI SOSIAL PENYANDANG DISABILITAS DI DINAS SOSIAL KABUPATEN SUMEDANG - Wahyudinata, Indra; Fadjri, Adjie Muhammad; Rohayatin, Ai; Maulana, Andriansah; Anisa, Dini; Ismaya, Rissa (LPPM UNSAP & FISIP UNSAP, 2024)
This research aims to find out how effective the implementation of Social Rehabilitation for Persons with Disabilities is at the Sumedang Regency Social Service. The method used in this research is qualitative method. Determining informants in this research used purposive sampling. There were three informants, consisting of: Service Secretary, Functional Officer, Young Social Rehabilitation Expert Worker, and Companion for Persons with Disabilities. The data collection techniques used were literature study and field study consisting of observation, interviews and documentation. Meanwhile, the data processing procedures in this research are data reduction, data display, data conclusion drawing/verification and triangulation. Based on the research results, it was concluded that this program had been implemented well but was not yet optimal. The inhibiting factors in program effectiveness are limited budget, inadequate infrastructure and incomplete program outreach. Efforts to overcome factors inhibiting the effectiveness of the program include identifying the use of funds, holding outreach with TKSK, and analyzing the condition of infrastructure to improve care and maintenance